1997
DOI: 10.1161/01.atv.17.2.331
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDLs Induce Massive Apoptosis of Cultured Human Endothelial Cells Through a Calcium-Dependent Pathway

Abstract: Oxidized LDLs are thought to play a central role in atherogenesis. Among their wide variety of biological properties, oxidized LDLs exhibit a cytotoxic effect on cultured vascular cells. Toxic doses of mildly oxidized LDLs elicited massive apoptosis in both primary and immortalized cultures of endothelial cells as shown by characteristic morphological and biochemical changes. Cytoplasmic and nucleic modifications (eg, chromatin condensation and nucleus fragmentation) were visualized by using electron and fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 48 publications
7
107
1
4
Order By: Relevance
“…Others in the field have also reported apoptosis of various eukaryotic cells upon exposure to borrelia spirochetes (40)(41)(42)(43)(44). Because infection with various species of RF spirochetes can result in cerebrovascular disease in humans (3)(4)(5)(6) and experimental animals (6,7,45,46) and the major virulence factor of borrelia spirochetes, the outer membrane lipoproteins (47), is capable of causing eukaryotic cell apoptosis (41), we hypothesized that bacterial lipoproteins from B. turicatae can cause brain endothelial cell apoptosis, similar to what has been reported for oxidized human lipoproteins (48)(49)(50)(51). We investigated this possibility in mice with relapsing-remitting infection and in vitro.…”
Section: Discussionmentioning
confidence: 73%
“…Others in the field have also reported apoptosis of various eukaryotic cells upon exposure to borrelia spirochetes (40)(41)(42)(43)(44). Because infection with various species of RF spirochetes can result in cerebrovascular disease in humans (3)(4)(5)(6) and experimental animals (6,7,45,46) and the major virulence factor of borrelia spirochetes, the outer membrane lipoproteins (47), is capable of causing eukaryotic cell apoptosis (41), we hypothesized that bacterial lipoproteins from B. turicatae can cause brain endothelial cell apoptosis, similar to what has been reported for oxidized human lipoproteins (48)(49)(50)(51). We investigated this possibility in mice with relapsing-remitting infection and in vitro.…”
Section: Discussionmentioning
confidence: 73%
“…In vitro studies had already shown that oxLDL exhibit cytotoxic e ects on cultured endothelial cells, but the type of cell death elicited remained unknown (Hessler et al, 1979). However, several authors recently reported increased apoptotic cell death of bovine aortic endothelial cells exposed to cholesterol oxides in culture (Lizard et al, 1996) and increased apoptosis (and possibly secondary necrosis) of HUVEC after exposure to oxLDL (Dimmeler et al, 1997a;Escargueil-Blanc et al, 1997). OxLDL-induced apoptosis is subsequent to a sustained and delayed peak in cytosolic calcium and is prevented by chelating extracellular calcium or by inhibiting calcium in¯ux (Escargueil-Blanc et al, 1997).…”
Section: Induction Of Pro-apoptotic Pathwaysmentioning
confidence: 99%
“…However, several authors recently reported increased apoptotic cell death of bovine aortic endothelial cells exposed to cholesterol oxides in culture (Lizard et al, 1996) and increased apoptosis (and possibly secondary necrosis) of HUVEC after exposure to oxLDL (Dimmeler et al, 1997a;Escargueil-Blanc et al, 1997). OxLDL-induced apoptosis is subsequent to a sustained and delayed peak in cytosolic calcium and is prevented by chelating extracellular calcium or by inhibiting calcium in¯ux (Escargueil-Blanc et al, 1997). Furthermore, ceramide generation by acid sphingomyelinase and activation of caspase-3 are indispensable for oxLDL-induced apoptosis (Harada-Shiba et al, 1998).…”
Section: Induction Of Pro-apoptotic Pathwaysmentioning
confidence: 99%
“…, in human epithelial cells (Escargueil-Blanc et al, 1997), and in malignant B cells (Shan et al, 1998). Decreases in Ca2+, may lead to apoptosis.…”
mentioning
confidence: 99%